AN ANALYSIS OF ONOMATOPOEIAS IN DONALD DUCK COMIC - Eliza, Tiara (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
This study discusses the types and meaning of onomatopoeias found in Donald Duck (2005) comic. In collecting the data, the writer used observational method and note taking technique (Sudaryanto, 1993). In analyzing the data, referential identity method (Sudaryanto, 1993) is applied. The types are analyzed by referring to Ullman’s (1962). The meanings are analyzed and strengthened by using the lexical meaning (Lyon, 1995) and contextual meaning (Ullmann, 1962) theories. The results show that there are two types of onomatopoeias found in the comic, the primary and secondary onomatopoeias. The primary onomatopoeia is the direct imitation of a sound produced by an object while secondary onomatopoeia comes from the sound combination produced by the specific characteristic of an object and its movement. In addition, the meanings of onomatopoeias derive from the lexical and contextual meanings. The lexical meaning refers to the dictionary meaning and the contextual refers to the context of an onomatopoeia in the comic line. From 15 data, the dominant type found is the secondary onomatopoeia